Retail of veterinary immunobiological preparations on the Ukrainian market of veterinary vaccines - I. V. Bushuieva; N. M. Borysenko (Zaporozhye State Medical University, 2020)
The purpose of the work is to determine the indicators of the peculiarities of the market of veterinary preparations; To carry out studies on the level of saturation and appropriate provision of the agricultural animals sector with veterinary drugs included in the List of Veterinary Immunobiological Drugs registered in Ukraine; to analyze the market of registered immunobiological drugs for medicinal forms; to research the market share of pharmaceutical companies - holders of registration certificates (Ukrainian and foreign) and companies - producers (Ukrainian and foreign) of this product; to summarize the dependence of the range of used vaccines for birds from their most frequent diseases in a particular farm and the general epizootic situation in the region. Materials and methods. We used synthetic, analytical, information retrieval, systematization, comparison, graphical, statistical, descriptive, generalization methods. The materials of the study were the Law of Ukraine "On Veterinary Medicine"; The list of veterinary immunobiological preparations registered in Ukraine as of 04/10/2019; official information of the State Statistics Service of Ukraine (Department of Agriculture and Environment Statistics) for 2018 - June 2019, reports of the consulting group Pro-Consulting and IndexBox Marketing. Results. The results of the study provide an opportunity to control the saturation of the market for veterinary immunobiological preparations; adjusting its volume and filling drugs, depending on the needs of the time; creating healthy competition between foreign market players and domestic producers; identification of the main market indicators (market conditions, demand, and consumption of immunological products), which will allow to make business development forecasts; assess the growth potential, opportunities and threats in the market; attracting to the Ukrainian market veterinary foreign firms -holders of registration certificates and firms - manufacturers of effective, affordable and quality vaccines in order to maintain a stable epizootic situation in rural areas, the private sector of the regions and the general well-being of the epizootic state in the state. Conclusions. Development, elements of systematization, comparison and generalization of the regulatory framework, namely: the Law of Ukraine "On Veterinary Medicine"The list of veterinary immunobiological preparations registered in Ukraine as of 04/10/2019; official information of the State Statistics Service of Ukraine (Department of Agriculture and Environment Statistics) for 2018 - June 2019, showed that at the present time there were opportunities in the Ukrainian market for new players to enter (from among domestic producers) who were more convenient for the distributor than for the manufacturer. Risks and barriers to entry to the market are mainly related to the high level of competition in the industry.